2021
DOI: 10.23937/2378-3419/1410146
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Safe Handling through Educating Nurses: A Pre-Experimental Study

Abstract: Introduction: Chemotherapy is a proven prodigy for the treatment of carcinoma but it can possess certain deleterious effects on the healthcare professionals while on constant exposure. Being frontline workers, nursing officers continuously come in contact with these chemotherapeutic agents. Hence, it is of paramount importance that nurses working in oncology unit have adequate knowledge and skill regarding safe handling of chemotherapeutic drugs. Materials and methods: Pre-experimental one group pretest post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…3,5,10,14,16,17 Providing educational activities on safely administering chemotherapeutic agents is an important strategy to help HCP maintain a safe practice environment. 10,16,18,19 In 2015, results of a national survey of 241 nurses and 183 pharmacy professionals showed that approximately 10% of the respondents had not participated in any educational activities addressing the safe handling of chemotherapeutic agents; approximately half of the respondents had participated in an educational activity on the topic before the survey, but the activity had occurred more than a year before the survey. 20 The educational activities should be based on the clinician's role 14 and should occur before handling hazardous medications and routinely thereafter.…”
Section: Performing Ivc Safelymentioning
confidence: 99%
See 2 more Smart Citations
“…3,5,10,14,16,17 Providing educational activities on safely administering chemotherapeutic agents is an important strategy to help HCP maintain a safe practice environment. 10,16,18,19 In 2015, results of a national survey of 241 nurses and 183 pharmacy professionals showed that approximately 10% of the respondents had not participated in any educational activities addressing the safe handling of chemotherapeutic agents; approximately half of the respondents had participated in an educational activity on the topic before the survey, but the activity had occurred more than a year before the survey. 20 The educational activities should be based on the clinician's role 14 and should occur before handling hazardous medications and routinely thereafter.…”
Section: Performing Ivc Safelymentioning
confidence: 99%
“…5 The activities may involve simulation, 18 blended learning, 18 or audiovisual presentations. 19 Providing educational activities on safely administering chemotherapeutic agents is an important strategy to help HCP maintain a safe practice environment.…”
Section: Performing Ivc Safelymentioning
confidence: 99%
See 1 more Smart Citation